The adoption of telemedicine by healthcare practitioners in South Africa - Margaret Cullen; Andre Calitz; Sasha Boucher; Prashna Buddan (Acta Commercii)
Orientation: Telemedicine plays an important role in patient-centred healthcare, diagnosing and treating diseases and developing treatment plans. It includes both provider-to-provider and provider-to-patient communication, which can be synchronous (telephone and video) or asynchronous (messaging and electronic consultations).